A superação do paradigma racionalista e a possibilidade de inclusão de comando mandamental na sentença condenatória - Lunelli, Carlos Alberto (Universidade do Vale do Rio do Sinos, 2006)
The condemnatory action of the civil process does not find a corresponding action in the material plan, which is why it does not fulfill the author’s pretension. The demand of its use in the civil process, as a condition to start an execution, in the pretensions related to the obligational law, is also related to the method employed by the process science. The scientific knowledge depends on the method that science uses. The spiritual science is not in the field of invention and its procedure differs from the natural one. The understanding must inform the knowledge in the social field. Therefore, it is inadequate the use of the natural sciences method when dealing with the process science. The incorporation of the exact sciences method by the spiritual science has its origin in the rationalistic thought, when a new conception of world and knowledge was developed in the Modern Age. In the field of Law, the influence of the Natural Law brought this peculiar dimension, where the necessary assertion of the human
Keywords: ação condenatória; ação mandamental; racionalismo; ciência processual; condemnatory action; rationalism; writ action; process science; Ciências Sociais Aplicadas